Care for women in a situation of violence: an institutionalist look. (30th September 2020) - Barbosa, J; Ferreira, B; Santos, D; Magalhães, F; Martins, G; Riquieri, M; Cordeiro, M; Silva, M; Lima, R; Andrade, M
Abstract: Objective: To know the dynamic processes that involve the production of care for women in situations of violence. Methods: Study of qualitative approach and cartographic inspiration based on the theoretical reference of Institutionalism that had as scenario a reference center for women in domestic violence located in Espírito Santo, Brazil. Six professionals who worked directly in the care of women participated in the research. Interventions were carried out, through seven workshops, using storytelling. The material production tools were narratives, the researcher's field diary and the collective field diary, which was built from the record and observation of all the participants in the study. The workshops were held at the center according to the availability of participants and lasted an average of 60 minutes. The meetings were recorded and later transcribed together with the notes of the field diaries, seeking, through a cartography, to give meaning to the experiences lived by the participants. Through the analysis of implication, it was possible to give visibility to the various relationships that constitute a certain reality, in which the researcher is involved. Results: The study pointed out that violence crosses all women influencing the production of care offered by professionals at the reference center. The narratives multiplied senses contributing to the problematization of the care offered, providing the qualification of other ways of thinking/acting in health. Conclusions: From an ethical-aesthetic-political paradigm it is possible to produce reflections that broaden the view of care for women in violent situations beyond biological issues, contributing with desirable productive processes in the prevention of violence and the promotion of health. Key messages: It gives visibility to micropolitical processes and contributes to the construction of policies for women's health capable of welcoming differences and singularities. It shows innovation for the field of qualitative health research, broadening the view on the care of women in situations of violence beyond biological issues.